2013
DOI: 10.1097/ta.0b013e31829d27b6
|View full text |Cite
|
Sign up to set email alerts
|

Measurable outcomes of quality improvement using a daily quality rounds checklist

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Evidence suggests that DVT screening may be unnecessary and not cost-effective in patients who receive appropriate prophylaxis 1517 . Furthermore, trauma centers are increasingly providing appropriate prophylaxis to trauma patients as efforts to reduce venous thromboembolism have received greater attention 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that DVT screening may be unnecessary and not cost-effective in patients who receive appropriate prophylaxis 1517 . Furthermore, trauma centers are increasingly providing appropriate prophylaxis to trauma patients as efforts to reduce venous thromboembolism have received greater attention 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review performed by Lane et al (2013)[ 4 ], which was recently updated[ 5 ], identified 13 best practices for ICU patient care rounds. These included implementing interprofessional rounds (physician, nurse, and pharmacist at minimum)[ 6 15 ]; standardizing practices[ 16 – 19 ]; defining roles for all participants[ 20 – 23 ]; using a structured tool[ 24 35 ]; reducing time spent on non-essential activities[ 17 , 18 ]; minimizing interruptions[ 36 38 ]; developing and documenting daily goals[ 22 , 31 , 39 , 40 ]; considering the best location of rounds (bedside vs. conference room) to optimize patient-centeredness and efficiency[ 36 , 41 43 ]; and establishing both an open and collaborative discussion environment[ 16 , 42 44 ]. All of these best practices were reported to potentially improve rounds either by increasing provider satisfaction, reducing rounding time, or improving patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…As a well-known example, after its worldwide introduction, the Surgical Safety Checklist by the World Health Organization has been recognised as a generally effective measure in order to increase patient safety in the operating room [ 14 ]. In 2013, a Quality Rounds Checklist could sustainably increase compliance with evidence-based standards and decrease complications in a trauma intensive care unit [ 34 ]. Through its multifaceted character they might be a cornerstone to improve patient safety sustainably.…”
Section: Discussionmentioning
confidence: 99%